2021
DOI: 10.1080/23273798.2021.1924387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prediction error on episodic memory retrieval: evidence from sentence reading and word recognition

Abstract: Prediction facilitates word processing in the moment, but the longer-term consequences of prediction remain unclear. We investigated whether prediction error during language encoding enhances memory for words later on. German-speaking participants read sentences in which the gender marking of the pre-nominal article was consistent or inconsistent with the predictable noun. During subsequent word recognition, we probed participants' recognition memory for predictable and unpredictable nouns. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Prior research has shown that in situations where a sentence context enables very specific predictions (like the ones used here), language users may pre-activate word form (e.g., DeLong et al, 2005;Fleur et al, 2020;Haeuser, Kray, & Borovsky, 2020;Van Berkum et al, 2005; but see Ito et al, 2017, andNieuwland et al, 2018, for failed replication; see Nieuwland, 2019, for critical discussion) and orthographical features of words (e.g., Balota et al, 1985;Kim & Lai, 2012;Laszlo & Federmeier, 2009;Luke & Christianson, 2012). In fact, we know that the stimuli used in this study did have such an effect on people in that they allowed for specific predictions regarding word forms (see Haeuser et al, 2020;Haeuser et al, accepted;Haeuser & Kray, 2021). We could speculate that, in the case of disconfirmed predictions, the early-emerging predictability effect may have reflected some early-emerging detection mechanism, signaling that the predicted word has not been encountered (cf., Kuperberg et al, 2020), or that vice versa, predictable words show a boost in pre-activation compared to other words which are at baseline (Frisson et al, 2017).…”
Section: Effects Of Predictability and Plausibility Violations On Sen...mentioning
confidence: 85%
See 1 more Smart Citation
“…Prior research has shown that in situations where a sentence context enables very specific predictions (like the ones used here), language users may pre-activate word form (e.g., DeLong et al, 2005;Fleur et al, 2020;Haeuser, Kray, & Borovsky, 2020;Van Berkum et al, 2005; but see Ito et al, 2017, andNieuwland et al, 2018, for failed replication; see Nieuwland, 2019, for critical discussion) and orthographical features of words (e.g., Balota et al, 1985;Kim & Lai, 2012;Laszlo & Federmeier, 2009;Luke & Christianson, 2012). In fact, we know that the stimuli used in this study did have such an effect on people in that they allowed for specific predictions regarding word forms (see Haeuser et al, 2020;Haeuser et al, accepted;Haeuser & Kray, 2021). We could speculate that, in the case of disconfirmed predictions, the early-emerging predictability effect may have reflected some early-emerging detection mechanism, signaling that the predicted word has not been encountered (cf., Kuperberg et al, 2020), or that vice versa, predictable words show a boost in pre-activation compared to other words which are at baseline (Frisson et al, 2017).…”
Section: Effects Of Predictability and Plausibility Violations On Sen...mentioning
confidence: 85%
“…In addition, unpredictable-somewhat plausible nouns showed a lateremerging positivity, an ERP effect that is sometimes associated with explicit recollection (compared to an initial stage of implicit, gist-wise memory without conscious recollection; Rugg & Curran, 2007). Hence, these findings suggest that unpredictable information that is somewhat plausible boosts short-term memory maybe because of the greater semantic elaboration associated with having predictions disconfirmed (i.e., prediction error; see Haeuser & Kray, 2021).…”
Section: Effects Of Predictability and Plausibility Violations On Lea...mentioning
confidence: 86%
“…Based on our findings, it seems that information coded in adjuncts (and unfocused information) is attended to a lower degree and it therefore often fails to reach readers’ awareness. Nevertheless, it is highly likely that other factors are at play here, such as information predictability ( Haeuser & Kray, 2021 ), a speaker’s experience ( Zwaan & Madden, 2005 ), context ( Bransford et al, 1972 ), imageability ( James, 1972 ), and so on. However, a thorough examination of such factors is already beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such an idea is aligned with findings reported in the previous literature. For example, Haeuser and Kray (2021) recently documented a clear relationship between RTs during processing (in a self-paced reading paradigm) and recognition memory (the longer the RTs, the better the subsequent recognition of the word).…”
Section: Discussionmentioning
confidence: 99%